Association between tear lactoferrin, lysozyme, albumin levels, and obstructive sleep apnea syndrome: a cross-sectional study - Wang, Bin; Hong, Chaoyang; Li, Wenwei (Frontiers in Medicine, 2025)
BackgroundObstructive Sleep Apnea Syndrome (OSAS) is associated with various ocular diseases, but its relationship with tear biomarkers for dry eye remains unclear. This study aimed to investigate these tear biomarkers and their correlation with OSAS.MethodsThis cross-sectional study was conducted at a tertiary hospital in Zhejiang Province from January 2021 to December 2022. Forty-one OSAS patients were enrolled. Tear lactoferrin, lysozyme, and albumin levels (exposure variables) were measured using ELISA, while OSAS (outcome variable) was diagnosed through polysomnography. Age, gender, and BMI were collected as covariates.ResultsBaseline characteristics (including age, gender, and BMI) showed no statistical differences between groups. No significant correlations were found between tear albumin (r = 0.10, p > 0.05), lactoferrin (r = 0.18, p > 0.05), lysozyme (r = −0.05, p > 0.05) levels and OSAS.ConclusionThis study found no significant correlation between dry eye tear biomarkers levels and disease severity in OSAS patients. Larger-scale studies are needed to validate these findings.